Herbivore dunging and endozoochorous seed deposition in a Mediterranean dehesa - Malo, J E; Jimenez, B; Suarez, F (JOURNAL OF RANGE MANAGEMENT, 2000)
Spatial patterns of herbivore defecation within grazing systems are important as they directly affect pasture growth and composition. These effects are partially linked to seed dispersal in dung, a little studied process. This paper focuses on: (1) quantification of dung and seeds deposited by herbivores in a Mediterranean grazing system, and (ii) analysis of the spatial variability of dung and seeds deposited within and among plant communities. We carried out year-long monthly quantifications of the depositions of rabbit (Oryctolagus cuniculus), fallow deer (Dama dama), red deer (Cervus elaphus), and cow (Bos taurus) dung to 32 plots distributed in Quercus rotundifolia Lam. and Fraxinus angustifolia Vahl woodlands, mixed scrub, and Cistus ladanifer L. scrub. We also quantified the germinable seed content of dung. The results revealed differences (p < 0.05) in dung deposition, varying (i) among the 4 species, (ii) within species (except for the red deer) among plant communities, and (iii) within plant communities. An average of 735 seeds/m(2) were returned to the soil via dung, with the highest numbers in open woodlands (870-1,888 seeds/m(2)) and the lowest numbers in scrubs (83-315 seeds/m(2)). Cows dispersed the most seeds (68%), followed by red deer (20%), rabbits (7%), and fallow deer (5%). Spatial variability in deposition led to accumulations of up to several thousand seeds at points covered by the dung. The effect of seed input to the seed bank and on vegetation may be low at large and medium-sized spatial scales, but it can be very important at small scales and for colonization processes.
Keywords: dispersal; dung; endozoochory; herbivores; Mediterranean pastures; Spatial pattern